2016
DOI: 10.1172/jci81568
|View full text |Cite
|
Sign up to set email alerts
|

RB1 deficiency in triple-negative breast cancer induces mitochondrial protein translation

Abstract: Triple-negative breast cancer (TNBC) includes basal-like and claudin-low subtypes for which no specific treatment is currently available. Although the retinoblastoma tumor-suppressor gene (RB1) is frequently lost together with TP53 in TNBC, it is not directly targetable. There is thus great interest in identifying vulnerabilities downstream of RB1 that can be therapeutically exploited. Here, we determined that combined inactivation of murine Rb and p53 in diverse mammary epithelial cells induced claudin-low-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 91 publications
5
128
1
1
Order By: Relevance
“…This is in stark contrast to multiple other mammary tumor models in which TICs were readily identified by our group and others (13,29,30,(60)(61)(62). One possible explanation is that AME tumor cells are dependent on estrogen signaling, thus unable to survive and proliferate in recipient mice without exogenous β-estradiol.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…This is in stark contrast to multiple other mammary tumor models in which TICs were readily identified by our group and others (13,29,30,(60)(61)(62). One possible explanation is that AME tumor cells are dependent on estrogen signaling, thus unable to survive and proliferate in recipient mice without exogenous β-estradiol.…”
Section: Discussioncontrasting
confidence: 64%
“…To identify TICs, mammary tumors were dissociated into single cells using collagenase digestion, lineage depleted, sorted on the basis of specific cell surface markers, serially diluted, mixed with matrigel, and transplanted into mammary glands of young, immunocompromised mice. Using these conditions, we previously identified TICs in mouse models of her2/neu, wnt1, mammary-specific rb loss, p53 loss, and pten/p53 double mutants (13,29,30 Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…Conversely, enhanced mitochondrial activity also increases ROS production associated with elevated oxygen consumption. The RB–E2F complex is known to directly suppress the expression of oxidative metabolism‐related enzymes and mitochondrial protein translation genes . Disruption of this complex therefore seems to provoke oxidative metabolism, such as the tricarboxylic acid cycle and FAO.…”
Section: Stem Cell‐like Features Induced By Rb Inactivationmentioning
confidence: 99%
“…As the mitochondrial energy metabolism provides distinct pro-survival benefits to diffuse large B-cell lymphomas (DLBCLs), pharmacological perturbation of the mitochondrial translation pathway with TIG is proved to be selectively toxic to DLBCL cell lines (Norberg et al, 2016). In addition, another group has identified that TIG could serve as a potential new therapeutic drug for treatment of retinoblastoma (RB1) -deficient breast cancer (Jones et al, 2016). Therefore, an important consideration in anti-cancer fields will be addressing mitochondrial signaling modulation with chemical compounds.…”
Section: Mitochondrion As a Target Of Tigmentioning
confidence: 99%